2013
DOI: 10.1063/1.4806969
|View full text |Cite
|
Sign up to set email alerts
|

The striped phases of ethylthiolate monolayers on the Au(111) surface: A scanning tunneling microscopy study

Abstract: Striped phases of ethylthiolate monolayers, corresponding to surface coverage in between 0.2 ML and 0.27 ML, were studied using high-resolution scanning tunneling microscopy. Striped phases consist of rows of Au-adatom-diethythiolate (AAD) aligned along the [112] direction. In the perpendicular [110] direction, the AAD rows adjust their spacing according to the surface coverage. A (5√3 × √3)-R30° striped phase with 0.27 ML thiolate and a (6√3 × √3)-R30° striped phase with 0.23 ML thiolate, both with long-range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 41 publications
4
60
0
Order By: Relevance
“…Au(CH3S)2 molecules have a tendency to form rows along the [112 ̅ ] direction for a broad range of coverages due to an attractive interaction between nearest neighbor molecules 6,13 . This row structure is rather common and observed for alkyl-thiolates with different alkane lengths 18,19 . An Au(CH3S)2 molecule can break off from the end of a Au(CH3S)2 row in a thermally activated process.…”
Section: Introductionmentioning
confidence: 59%
“…Au(CH3S)2 molecules have a tendency to form rows along the [112 ̅ ] direction for a broad range of coverages due to an attractive interaction between nearest neighbor molecules 6,13 . This row structure is rather common and observed for alkyl-thiolates with different alkane lengths 18,19 . An Au(CH3S)2 molecule can break off from the end of a Au(CH3S)2 row in a thermally activated process.…”
Section: Introductionmentioning
confidence: 59%
“…By acquiring images with different bias voltages from -1 V to 1 V with the tunnel current fixed, we found that switching is independent of the bias polarity, but becomes more effective as the bias gets lower corresponding to smaller tip-molecule distances. From experiments with Audiethylthiolate, we know that thermally-induced cis-trans isomerization does not take place even at room temperature [23] . This implies an activation barrier higher than 25 meV.…”
mentioning
confidence: 99%
“…The distance between neighboring two rows is coverage dependent. 49,52,53 One striped phase can change into another when the molecular coverage changes. Also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%